Description of the female of Leptagrion itabaiana Vilela, Lencioni & Santos, 2021 (Odonata: Coenagrionidae) from Serra of Itabaiana National Park, Northeastern Brazil - Farias, Antonio Bruno Silva; Ventura, Iza Mayra Castro; Vilela, Diogo Silva; Santos, Jean Carlos (Zootaxa, 2024)
The unknown female, Leptagrion itabaiana Vilela, Lencioni & Santos, 2021 was described, illustrated, and diagnosed based on two specimens collected in the Serra of Itabaiana National Park (♀, Brazil, Sergipe, Areia Branca, Serra of Itabaiana National Park, -10.7484, -37.3390, 221 m, 24.v.2023, A. B. S. Farias leg., UFS). Leptagrion itabaiana female can be separated from their congeners by the following characteristic combinations: shape of the prothoracic hind lobe, body size, and ovipositor valves size.